SYNTHESIS AND CHARACTERIZATION OF pH-SENSITIVE N-SUCCINYL CHITOSAN HYDROGEL AND ITS PROPERTIES FOR BIOMEDICAL APPLICATIONS - Bashir, Shahid; Teo, Yin Yin; Ramesh, S.; Ramesh, K.; Rizwan, Muhammad (Journal of the Chilean Chemical Society, 2019)
Natural polymers have been widely used in different fields specifically in pharmaceutical industry due to their biocompatibility, biodegradability, and less toxicity properties. Among these polymers, chitosan is a potentially pursued biomaterial. However, limited solubility of chitosan in water creates significant barrier in realizing its applications as a biomaterial. Modification of chitosan helps to overcome this barrier with improved solubility in water. In this study, N-succinyl chitosan was synthesized from the chemical reaction of chitosan and succinic anhydride via Schiff base mechanism by using glutaraldehyde as a crosslinking agent. N-succinyl chitosan is water soluble, biocompatible, biodegradable, and less toxic. The physico-chemical properties of NSC and prepared hydrogel were characterized by using Fourier transform infrared (FTIR) spectroscopy, Nuclear Magnetic Resonance Spectroscopy (NMR), X-ray diffraction (XRD) analysis, and differential scanning calorimetry (DSC). The surface morphology was investigated through Field emission scanning electron microscopy (FESEM). All these results confirmed the successful synthesis of N-succinyl chitosan and its hydrogel. Moreover, the mechanical properties of the hydrogel were evaluated using rheometer and found that hydrogel has significant potential to be used in the biomedical field. In addition, the swelling properties of the hydrogel were also studied in buffer solutions of pH 1.2 and 7.4. These results endorsed its applications as a drug delivery carrier.